Health among youth and young adults born in the nordic countries to immigrant parents- a scoping review - Naima Said Sheikh; Guido Philipp Emmanuel Biele; Melanie Lindsay Straiton; Marte Karoline Råberg Kjøllesdal (BMC Public Health)
Abstract Introduction A considerable number of individuals born in the Nordic countries to immigrant parents are now entering youth and young adulthood, but we have limited knowledge about their health. This scoping review aimed to map and summarize existing knowledge on the health of this group. Methods This research followed guidelines from the Joanna Briggs Institute. The literature search was performed in the databases Ovid Medline, Embase, APA PsycInfo, CINAHL, Scopus, SveMed+, Cochrane Central Register of Controlled Trials Issue, and Epistemonikos. Two researchers screened titles and abstracts of all records, and then full-texts of potentially relevant studies. Any disagreements were solved by discussion. Reference lists of the included studies were screened for additional relevant articles. Included articles should report on health outcomes among persons aged 16–30 years, born in a Nordic country to immigrant parents. Evidence was extracted and summarized. Results The initial search resulted in 2452 unique records. A total of 11 articles were included in the final scoping review. Most of the studies were on mental health and concluded that descendants of immigrants had higher levels of self-reported mental health problems than native-background youths and young adults. They were, however, less likely to use mental health services. Conclusion Available studies suggest that young adults born in the Nordics to immigrant parents have a greater burden of mental health problems but use mental health services less, than natives. Further studies on the reasons for this are warranted to elucidate possible action points.